Proposta de melhoria em um processo de pronto atendimento utilizando a abordagem lean healthcare 4.0 - Delecrodio, Thays Aparecida Vendramin (2021)
Since the 2010s, the health issue has received worldwide attention, therefore, many hospitals have resorted to improving processes, using methods such as the lean production system, which is called Lean Healthcare in the health area. Currently, such practices have been increased with the digitization and integration of processes, which enable the definition of what came to be called Healthcare 4.0. For these considerations, the objective of this study was to analyze problems faced by patients and providers of medical emergency service and, through the application of Lean Healthcare 4.0 principles and techniques, to propose improvements in the current conditions of the care flow of an Emergency Room. To this end, field research was carried out using the Delphi Method to verify the applicability of the theoretical flow of assistance developed to real-world situations. It is hoped that this research will contribute theoretically, practically and conceptually to future studies on Lean Healthcare 4.0.